TRANSFORMING AGRICULTURE THROUGH ARTIFICIAL INTELLIGENCE: A TECHNICAL ANALYSIS - Vinod Upputuri, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The integration of Artificial Intelligence in agriculture represents a transformative advancement in farming practices, offering unprecedented opportunities for optimization and sustainable food production. This technical article examines the implementation of AI technologies across the agricultural sector, encompassing machine learning systems, computer vision applications, IoT infrastructure, and robotics automation. The article investigates the technical architecture, integration methodologies, and real-world case studies from both large-scale and small-holder farming operations. Through comprehensive examination of implementation challenges, emerging technologies, and socioeconomic impacts, this article demonstrates how AI adoption is revolutionizing traditional farming practices while addressing critical issues of resource efficiency, environmental sustainability, and farm productivity. The article highlights the importance of accessible solutions for small-scale farmers and emphasizes the need for culturally contextualized implementation strategies to ensure widespread adoption and sustainable agricultural development.